2019
DOI: 10.3390/ijms20010190
|View full text |Cite
|
Sign up to set email alerts
|

Interferon β-Mediated Protective Functions of Microglia in Central Nervous System Autoimmunity

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) leading to demyelination and axonal damage. It often affects young adults and can lead to neurological disability. Interferon β (IFNβ) preparations represent widely used treatment regimens for patients with relapsing-remitting MS (RRMS) with therapeutic efficacy in reducing disease progression and frequency of acute exacerbations. In mice, IFNβ therapy has been shown to ameliorate experimental autoimmune encephalomyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 209 publications
(252 reference statements)
1
17
0
Order By: Relevance
“…However, studies based on IFNAR signaling cannot pinpoint the functional contribution of IFN-␣ and IFN-␤ during neuroprotection. Moreover, similar to its protective actions in MS (Scheu et al, 2019), exogenous administration of IFN-␤ following spinal cord injury improves functional recovery in mice, in part by reducing lipid peroxidation and inflammatory cytokines (Gok et al, 2007;Sandrow-Feinberg et al, 2010). This highlights the complex role of IFN-␤ during secondary injury and CNS repair.…”
Section: Discussionmentioning
confidence: 79%
“…However, studies based on IFNAR signaling cannot pinpoint the functional contribution of IFN-␣ and IFN-␤ during neuroprotection. Moreover, similar to its protective actions in MS (Scheu et al, 2019), exogenous administration of IFN-␤ following spinal cord injury improves functional recovery in mice, in part by reducing lipid peroxidation and inflammatory cytokines (Gok et al, 2007;Sandrow-Feinberg et al, 2010). This highlights the complex role of IFN-␤ during secondary injury and CNS repair.…”
Section: Discussionmentioning
confidence: 79%
“…As a therapeutic agent, IFNβ represents a widely used treatment regimen for patients with relapsing-remitting MS (RRMS) [92] and shows treatment efficacy by reducing disease progression and also frequency of exacerbation. In animal experiments, induction of endogenous IFNβ by polyinosinic:polycytidylic acid [poly(I:C)] treatment diminished the severity of EAE, and genetic deletion of IFNβ or its receptor in contrast enhanced clinical score, with more extensive CNS inflammation and demyelination [93]. Treament with IFNβ also reduced axonal damage in a cerebellar slice culture assay with LPS stimulation [94].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Previously, Toll/interleukin-1 receptor domain-containing adapter inducing IFN-β (TRIF) de cient microglia exhibited an increased threshold for activation of interferon-regulated genes, suggesting that IFN-β may enhance phagocytic activity [37]. In experimental autoimmune encephalomyelitis, IFN-β producing microglia mediated an enhanced removal of myelin debris compared to IFN-β non-producing microglia [38]. Indeed, we observed that STING-activated microglia exhibit a superior phagocytic capacity, and IFN-β might guide positioning of microglia in the in amed central nervous system during chronic stress.…”
Section: Discussionmentioning
confidence: 99%